Applying Paul’s Theological and Ethical Teachings in Romans 12:1 to an African Context - Isaac Boaheng (Indonesian Academy of Social and Religious Research (IASRR), 2023)
One of the key challenges facing Christianity in contemporary Africa is ineffective discipleship. The African church has won many converts in recent times and yet, the continent is among the least performing continents in terms of socio-economic development. The reason for this observation is that many African Christians consider Christianity as a religion of the heart and consequently, do not care so much about what they do in the public arena. In a context like this, Paul’s concept of the transformed life (explained in Romans 12:1) has the potential of correcting misconceptions about Christianity and empowering African Christians to engage the public sphere with their faith. The purpose of this paper is to conduct a textual analysis of Romans 12:1 to develop Christian ethics for (Africa) believers. The paper used a literature-based research approach and collected data from such sources as commentaries, articles and dissertations. The main thesis is that living a sacrificial life involves a total dedication to God in response to his gracious mercies manifested toward the believer. The paper contributes to Christian ethics, Pauline studies and African Christianity.